Perspectives on Reincarnation: Hindu, Christian, and Scientific - Jeffery D. Long (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The articles in this volume, all by leading scholars, examine the topic of rebirth, or reincarnation, from a wide range of perspectives. The main focus of most of the articles is the idea of rebirth as found in Hindu texts and traditions. There are also articles exploring Christian responses to the idea of rebirth as well as expressions of the idea of rebirth in the Western world (such as in the thought of poet William Butler Yeats and in an American context). There are also philosophical and theological articles arguing both for and against the idea of rebirth, as well as articles which take a more historical or literary approach to this topic. The shared thread unifying all of these articles is the idea that rebirth is an important idea that holds great fascination for many. While the primary focus is on Hindu and Christian expressions of or responses to this idea, there are also articles that engage with scientific thinking on this topic, and one which engages with Buddhism as well. In short, this volume is an interdisciplinary and cross-cultural, and cross-traditional exploration of the topic of reincarnation that should appeal to a wide array of readers.